Central Industrial District: First plan of sustainable development of Poland (Economic and Political Thought, 2019)
The Central Industrial District [Centralny Okręg Przemysłowy (COP)]has been the object of scientific deliberations, analyses and research worksfor years. The study presents its origin and various stages of the projectimplementation. The silhouette of the main founder of COP, EugeniuszKwiatkowski, the Minister of the Treasury and the Deputy Prime Ministeris presented, outlining his main idea, which led him to create a strategy forPoland. Mentioning the most important investments carried out in COP, theauthor shows their considerable momentum and scope. The ability to engagehuman capital on such a large scale shows the character of that generation,their great desire to build a safe and prosperous country for the good of futuregenerations. The establishment of the Central Industrial Region was Polandand Poles’ success, raising their quality of life and providing a guarantee ofsustainable development of the national economy. The COP infrastructureand some industrial plants built there have been used by present generationsuntil now. The study compares COP to the Strategy for Responsible Development,defining common features and indicating the directions of Poland'seconomic development in both historical periods.
Keywords: COP, BGK, Strategy for Responsible Development